Tinjauan Yuridis Penyidikan Tindak Pidana Perikanan di Laut Oleh Penyidik Polisi - Made Mahardika; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
Starting from 2004, the illegal fishing sector is now supervised by Fisheries Law. Fishermen generally use a variety of fishing gear to pull fish from the waters, but any means that can damage the marine ecosystem in the long run are prohibited. The formulation of the problem in this study is, How are the arrangements for investigations carried out by investigators against perpetrators of fisheries crimes? And what is the authority in investigating fisheries crimes? This research aims to determine who has jurisdiction to investigate fishing offenses and how the police carry out such investigations. Specifically, a normative law study was used. Investigators from the Indonesian National Police (Polri) have the authority to investigate illegal activities in designated areas of Indonesia in accordance with the Criminal Procedure Law and other legal regulations. The procedure for investigating unlawful acts in the fisheries sector is based on the authority of Polri investigators as stipulated in Article 73 paragraph 4 Fisheries Law.